UPAYA PEMERINTAH DESA DALAM MENANGGAPI DAMPAK COVID-19 DI DESA SUKAJAYA KECAMATAN SUMEDANG SELATAN KABUPATEN SUMEDANG - Hidayati, Atikah Nur (Jurnal Politik Pemerintahan Dharma Praja, 2020)
The aim of this research is to identify the Village Government’s efforts in responding to impacts of Covid-19 in Sukajaya Village, Sub-district of South Sumedang, Sumedang Regency. This research is a descriptive qualitative research based on in-depth interviews method with the parties involved in it. The efforts of the Village Government which are in line with the directions of the central and regional policies need to be responded well by the society, because if the society do not give any good respond to any kind of Village Government’s policies in order to handle the impact of Covid-19, it will not show any good result. The Village Government also need to respond any suggestion, criticism from society as well to syncronize the policies and its aims in order to achieve policies effectivity as expected by various parties.